Drug repurposing strategy targeting serotonin-gated ion channels - Rodriguez Araujo, Noelia (2022)
The need to achieve a greater understanding of the diverse array of medical problems imposes a kind of conducting force capable of pushing this continuously shifting exploration border towards areas of greater confidence. The science and the medical practice digging their backgrounds through hypotheses, experimental verifications, and subsequent interpretations are presently getting the input of Translational Medicine viewed as a goal of biomedical research aimed at offering better control tools. Something that is closely linked to the origins of the very medicine. The transition between basic and clinical research is complex requiring appropriate crosstalk helpful enough for the input/output relationship to become fruitful. Partly because the in vitro experiments and preclinical studies do not necessarily mirror the clinical situation to sensibly translate the “truth” emerging from laboratory data. This is particularly relevant when trying to develop new biomarkers, potentially predictive scoring systems, biostatistical procedures for combined endpoints, and mostly, the efforts towards the availability of novel therapeutic approaches. Regardless of the precise situation, intermingled communication between players from different fields is necessary, if we are about to establish new conceptual and methodological frameworks likely to facilitate a better theoretical/practical approach. To some extent, it constitutes a sort of burst of the biomedical sciences into the clinical scenario aimed at validating the knowledge arising in the laboratory to become part of some clinical practice or guidelines for health policies, with all the implications therein. Conversely, many clinical observations raise questions that can be elucidated from the experimental ground, as a valuable way of affording some feedback on this interactive process. The way ahead appears as long as challenging, given that the bulk of the investigative work carried out in our setting has been mostly performed in self-confined compartments (biomedical, clinical, and public health). Purportedly, we have lastly realized that field-specific speeches concentrated on themselves end up hindering the portrayal of problems in their different facets, as well as the way of formulating investigative designs addressed to provide improved alternatives